Unmanned aerial remote sensing UAS for environmental applications - Green, David R., 1954-; Gregory, Billy J.; Karachok, Alexander (Boca Raton : CRC Press, 2020)
Unmanned Aircraft Systems (UAS) are a rapidly evolving technology with an expanding array of diverse applications. In response to the continuing evolution of this technology, this book discusses unmanned aerial vehicles (UAVs) and similar systems, platforms and sensors, as well as exploring some of their environmental applications. It explains how they can be used for mapping, monitoring, and modeling a wide variety of different environmental aspects, and at the same time addresses some of the current constraints placed on realizing the potential use of the technology such as s flight duration and distance, safety, and the invasion of privacy etc. Features of the book: Provides necessary theoretical foundations for pertinent subject matter areas Introduces the role and value of UAVs for geographical data acquisition, and the ways to acquire and process the data Provides a synthesis of ongoing research and a focus on the use of technology for small-scale image and spatial data acquisition in an environmental context Written by experts of the technology who bring together UAS tools and resources for the environmental specialist Unmanned Aerial Remote Sensing: UAS for Environmental Applications is an excellent resource for any practitioner utilizing remote sensing and other geospatial technologies for environmental applications, such as conservation, research, and planning. Students and academics in information science, environment and natural resources, geosciences, and geography, will likewise find this comprehensive book a useful and informative resource.
From radio controlled model aircraft to drones -- Aquatic vegetation monitoring with UAS -- Unmanned aerial vehicles for riverine environments -- Low-Cost UAVs for environmental monitoring, mapping, and modelling of the coastal zone -- Unmanned aerial system applications to coastal environments -- UAV image acquisition using structure from motion to visualise a coastal dune system -- Monitoring, mapping, and modelling saltmarsh with UAVs -- Autonomous UAV-based insect monitoring -- UAV imagery to monitor, map, and model a vineyard canopy to aid the application of precision viticulture to small-area vineyards -- Forest ecosystem monitoring using unmanned aerial systems -- Monitoring oil and gas pipelines with small UAV systems -- Drone-based imaging in archaeology : current applications and future prospects -- Unmanned aerial system (UAS) applications in the built environment : towards automated building inspection procedures using drones -- The application of UAVs to inform coastal area management -- From land to sea : monitoring the underwater environment with drone technology -- A question of UAS ground control : frequency and distribution -- Launch and recovery system for improved fixed-wing UAV deployment in complex environments.
OCLC-licensed vendor bibliographic record.
Keywords: Environmental monitoring -- Remote sensing; Environmental mapping -- Remote sensing; Drone aircraft in remote sensing; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Environmental Engineering & Technology; TECHNOLOGY / Remote Sensing